The mobile application hacker's handbook - Chell, Dominic; Erasmus, Tyrone; Colley, Shaun; Whitehiuse, Ollie (Wiley, 2015)
This is a comprehensive guide to securing all mobile applications by approaching the issue from a hacker's point of view. It provides expert guidance toward discovering and exploiting flaws in mobile applications on the iOS, Android, Blackberry, and Windows Phone platforms. You will learn a proven methodology for approaching mobile application assessments, and the techniques used to prevent, disrupt, and remediate the various types of attacks. Coverage includes data storage, cryptography, transport layers, data leakage, injection attacks, runtime manipulation, security controls, and cross-platform apps, with vulnerabilities highlighted and detailed information on the methods hackers use to get around standard security.